Production and Foreign Investment Affected by Brexit - Walid Y. Alali; Haider Ellalee (SSRN, 2019)
We resolve several scenarios of post-Brexit using a multi-country simulations model of neoclassical growth. We started by assuming the UK unilaterally imposed much tighter restrictions on foreign direct investment and trade with other EU countries. Then we assume the European Union imposes and retaliates against the United Kingdom's same restrictions. In the final scenario, the UK has reduced restrictions on other countries through the post-Brexit transition period. The model predictions depend mainly on the policy response to MNCs' investments in technology capital, knowledge accumulated from investments in brands, R&D and organisations used concurrently in their foreign and domestic operations.
Keywords: 330; Brexit; Economic growth; Investment; FDI; Trade Policy; International Trade; Economic Integration; Multinational Firms; Management of Technological Innovation and R&D